The relationship between dyslipidemia and chronic liver disease, with the mediating role of depressive symptoms - Li, Wencheng; Zhou, Youlan; Li, Qingni; Wang, Deqiang (Frontiers in public health, 2025)
BackgroundDyslipidemia and chronic liver disease (CLD) remain major global health challenges with high morbidity and mortality rates. Although extensively studied, the association between dyslipidemia and CLD remains incompletely elucidated. Depressive symptoms, an increasingly prevalent comorbidity, have been widely implicated in both conditions. This study aimed to investigate the bidirectional effects between dyslipidemia and CLD and the mediating role of depressive symptoms in their association.MethodsWe recruited 6,926 participants aged ≥45 years from the China Health and Retirement Longitudinal Study (CHARLS). It used Logistic regression and mediation analysis to examine the bidirectional link between dyslipidemia and CLD, and the mediating role of depressive symptoms.ResultsThe median age was 58.7 years. Among participants, 222 were diagnosed with CLD and 1,883 with dyslipidemia. After adjusting for confounders, individuals with dyslipidemia exhibited an 81% higher risk of CLD (OR = 1.81, 95% CI = 1.32–2.46). Conversely, those with CLD had an 81% elevated risk of dyslipidemia (OR = 1.81, 95% CI = 1.33–2.46). Depressive symptoms mediated a statistically significant yet modest proportion of the bidirectional association (mediation proportions: 2.91% for the path from dyslipidemia to CLD; 2.54% for the path from CLD to dyslipidemia).ConclusionA bidirectional relationship exists between dyslipidemia and CLD, partially mediated by depressive symptoms. While lipid regulation and CLD management are crucial, causal inferences are limited by the cross-sectional design. Future longitudinal or experimental studies are warranted to establish causality.